The freshwater isopod Asellus aquaticus as a model biomonitor of environmental pollution: A review. (November 2019) - O'Callaghan, Irene; Harrison, Simon; Fitzpatrick, Dara; Sullivan, Timothy
Abstract: Anthropogenic substances pollute freshwater systems worldwide, with serious, long-lasting effects to aquatic biota. Present methods of detecting elevated levels of trace metal pollutants are typically accurate but expensive, and therefore not suitable for applications requiring high spatial resolution. Additionally, these methods are not efficient solutions for the determination of long-term averages of pollution concentration. This is the rationale for the implementation of a biomonitoring programme as an alternative means of pollutant detection. This review summarises recent literature concerning the past and potential uses of the benthic isopod Asellus aquaticus as a biomonitor for pollution in freshwater systems. Recent studies indicate that A. aquaticus is well suited for this purpose. However, the mechanisms by which it bioaccumulates toxins have yet to be fully understood. In particular, the interactions between coexisting trace metal pollutants in the aquatic environment have only recently been considered, and it remains unclear how a biomonitoring programme should adapt to the effects of these interactions. It is evident that failing to account for these additional stressors will result in an ineffective biomonitoring programme; for this reason, a comprehensive understanding of the bioaccumulation mechanisms is required in order to reliably anticipate the effects of any interferences on the outcome. Graphical abstract: Image 1 Highlights: Asellus aquaticus is known to bioaccumulate trace metals. A. aquaticus has been suggested as a potential biomonitor for metal pollutants. A biomonitoring programme could act as an early warning system for pollution events. Metal uptake and sequestering mechanisms are still poorly understood. Antagonistic effects of metals must be better understood for implementation to succeed. Abstract : Capsule: "The benthic isopod, Asellus aquaticus, may be an ideal biomonitor for freshwater pollution."